Thermodynamic Behavior of Ce Compounds Close to a T ->0 Critical Point - Sereni, J.G. (2013)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina